Penerapan Sistem Informasi Akuntansi terhadap Kinerja Karyawan pada PT.AJINOMOTO Cabang Bengkulu Tahun 2022-2024 - Herdyasnyah, Herdyasnyah; Riswandi, Pedi; Arnova, Iwin (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the impact of implementing an Accounting Information System (AIS) on employee performance at PT. Ajinomoto Bengkulu Branch during the period 2022–2024. The research focuses on two core systems: Handi HTS and the Ajinomoto Web Portal, both of which support data processing, reporting, and performance monitoring. The main issue addressed is the suboptimal use of AIS due to limited hardware, network constraints, and varying user competencies. This qualitative descriptive study involved in-depth interviews with 15 informants from various organizational levels, including managers, supervisors, and chief salespersons. Data were collected through interviews, direct observation, and focus group discussions, then analyzed using thematic data reduction and interpretation techniques. Findings reveal that the application of AIS through Handi HTS and the Web Portal has significantly enhanced employee performance across five key dimensions: time efficiency, work quality, productivity, job satisfaction, and competency. Both systems were assessed to provide accurate, real-time, and user-friendly information that supports flexible work arrangements and faster decision-making. In addition, integrated features such as automatic reporting, performance dashboards, and data synchronization between departments contributed to greater operational efficiency and transparency. In conclusion, the implementation of a well-integrated AIS has played a crucial role in improving employee effectiveness, supporting strategic decisions, and promoting a more professional work environment at PT. Ajinomoto Bengkulu. The study highlights the importance of aligning technology with user capabilities to optimize organizational outcomes.